Valuing the closely held firm - Long, Michael S.; Bryant, Thomas A. (Thomas Alex), 1953- (Oxford ; New York : Oxford University Press, 2008)
The book provides the technical and quantitative support to demostrate the various valuation approaches.
Why bother valuing a private business? -- Is it a business, or just a pile of assets? special questions and adjustments in the valuation of closely held firms -- Valuation when a firm is not a going concern -- Valuation of a going concern -- Growth options and valuation -- Inflation and valuation measurement -- Calculating the discount rate for closely held firms -- Planning to buy? considerations from the other side of the sale -- The exit strategy -- What we know, where to go next.
Includes bibliographical references (p. 253-255) and index.
aug 28/05/13
Loans
Keywords: Close corporations -- Valuation; Business enterprises -- Valuation; Small business -- Valuation